EXPERT SYSTEM FOR DETECTING AND DIAGNOSING CAR ENGINE OVERHEATING FAULT USING DYNAMIC CONTROL SYSTEM (DCS) - Lanlege, David Ibitayo; Adeniyi, Adeola Isaac; Wachin, Abdullahi A.; Olojede, Abayomi Opeyemi (FUDMA JOURNAL OF SCIENCES, 2025)
Dynamic Control Systems (DCS) can be applied in detecting and diagnosing car engine overheating and can be continuously implemented to serve fields such as Applied Mathematics, among others. Car engine overheating is a sequence of diagnostic processes that deploys expertise. In addition, Advanced System is one of the leading Artificial Intelligence techniques that have been adopted to handle such tasks. This paper presents the imperatives for an advanced system in developing Dynamic Control Systems for detecting and diagnosing car engine overheating through input and output requirements of constructing successful differential equations. Thus, DCS provides input and output equations in the form of Matrix/Vector State Space Representation (MSSR) via mathematical Differential Equations in the form of the DCS approach.
Keywords: Car Engine Overheating; Generating Function; Input and Output equations; Differential Equations; Matrix/Vector State Space Representation (MSSR); Dynamic Control Systems (DCS); State Equation